Population Genetics And Distribution Of Two Sympatric Frog Species In Peninsular Malaysia, Fejevarya Cancrivora (Gravenhorst, 1829) And Fejevarya Limnocharis (Boie, 1834) - Hurzaid, Amirah (2013)
A population genetic study of two sympatric frog species in Peninsular Malaysia, Fejevarya cancrivora and F. limnocharis was conducted using the highly evolving D-loop segment of mtDNA. The genetic survey was conducted on six populations (26 individuals) of F. cancrivora from northern Peninsular Malaysia and 16 populations (106 individuals) of F. limnocharis from northwest, central west and east of Peninsular Malaysia. In general, F. cancrivora showed very high genetic variation for Pulau Langkawi population and lack of variation for the Jitra population. The constructed Neighbour Joining (NJ) and Maximum Parsimony (MP) phylogenetic trees showed similar topology, with the Pulau Langkawi population forming its own clade. It is suggested that the deep branching of Pulau Langkawi populations with high mutation rates from major haplotypes may be caused by the extension time of isolation of populations which had experienced bottleneck followed by genetic drift. As for F. limnocharis, mean haplotype and nucleotide diversity was low over all samples (h = 0.471 ± 0.27; π = 0.004 ± 0.0000